Serotonin, Amygdala and Fear: Assembling the Puzzle - Bocchio, Marco; McHugh, Stephen B.; Bannerman, David M.; Sharp, Trevor; Capogna, Marco (Frontiers in Neural Circuits, 2016)
The fear circuitry orchestrates defense mechanisms in response to environmental threats. This circuitry is evolutionarily crucial for survival, but its dysregulation is thought to play a major role in the pathophysiology of psychiatric conditions in humans. The amygdala is a key player in the processing of fear. This brain area is prominently modulated by the neurotransmitter serotonin (5-hydroxytryptamine, 5-HT). The 5-HT input to the amygdala has drawn particular interest because genetic and pharmacological alterations of the 5-HT transporter (5-HTT) affect amygdala activation in response to emotional stimuli. Nonetheless, the impact of 5-HT on fear processing remains poorly understood. The aim of this review is to elucidate the physiological role of 5-HT in fear learning via its action on the neuronal circuits of the amygdala. Since 5-HT release increases in the BLA during both fear memory acquisition and expression, we examine whether and how 5-HT neurons encode aversive stimuli and aversive cues. Next, we describe pharmacological and genetic alterations of 5-HT neurotransmission that, in both rodents and humans, lead to altered fear learning. To explore the mechanisms through which 5-HT could modulate conditioned fear, we focus on the rodent basolateral amygdala (BLA). We propose that a circuit-based approach taking into account the localization of specific 5-HT receptors on neurochemically-defined neurons in the BLA may be essential to decipher the role of 5-HT in emotional behavior. In keeping with a 5-HT control of fear learning, we review electrophysiological data suggesting that 5-HT regulates synaptic plasticity, spike synchrony and theta oscillations in the BLA via actions on different subcellular compartments of principal neurons and distinct GABAergic interneuron populations. Finally, we discuss how recently developed optogenetic tools combined with electrophysiological recordings and behavior could progress the knowledge of the mechanisms underlying 5-HT modulation of fear learning via action on amygdala circuits. Such advancement could pave the way for a deeper understanding of 5-HT in emotional behavior in both health and disease.